State of the world's oceans - Allsopp, Michelle (Springer, 2009)
"This book provides a contemporary overview of the world's oceans. It identifies and describes the various problems which continue to threaten environmental quality and biodiversity, ranging from overfishing to the complex changes which could take place as a result of global climate change. Written by scientists working at the Greenpeace Research Laboratories at the University of Exeter in the UK, it is based upon the latest published scientific information. It draws upon the considerable and unique experience of Greenpeace as an organisation working on a diverse array of marine conservation issues at the international scale. The book is designed to serve a wide readership, both as a source of reliable information and as an introduction to the wide literature which exists on marine conservation issues. It is designed to be accessible by those pursuing academic studies as well as those with a more general interest in the factors which are shaping our oceans. As well as identifying the many problems, the book also outlines the ways in which the foundations and building blocks for clean, healthy and biodiverse seas can be provided, especially through the development of a global network of marine reserves."--BOOK JACKET.